Effect of Financial Performance, Good Corporate Governance and Corporate Size on Corporate Value in Food and Beverages - Manurung, Elon; Effrida, Effrida; Gondowonto, Andreas James (International Journal of Economics and Financial Issues, 2019)
This study aims to determine the effect of financial performance, good corporate governance, and company size as an independent variable on company value as a dependent variable on food and beverage companies listed on the Indonesia Stock Exchange in 2015 - 2017. This study uses a quantitative approach. Sources of data in this study came from the company's financial statements obtained on the website page www.idx.co.id. The population in this study were 26 manufacturing companies in the food and beverage industry which were listed on the Indonesia Stock Exchange in 2015-2017. Based on the specified sample selection criteria, there are 16 companies that meet these criteria and qualify as a research sample. Based on the results of the chow test and the Hausman test, the most appropriate model used in the panel data regression of this study is the fixed effect model. Based on the results of regression in the company used as a sample in this study showed the adjusted R ^ 2 value of 0.977623. This means that 97.7623% of the dependent variable is the value of the company can be explained by the independent variables, namely financial performance, institutional ownership, managerial ownership and company size. While the remaining 2.2377% is explained by other factors outside the independent variables in the study. Keywords: Financial Performance, Good Corporate Governance, Company Size, The value of the company JEL Classifications: E10, E32, E60 DOI: https://doi.org/10.32479/ijefi.8828